The Influence of Debt to Equity Ratio and Return on Equity on Company Value in Food and Beverage Subsector Manufacturing Companies Listed on the BEI in 2020-2022 - M. Hidayatul Ihsan; Nia Kurniasari (Formosa Journal of Social Sciences (FJSS), 2024)
The purpose of this study is to analyse the relationship between Y, debt-to-equity ratio, and return on equity for food and beverage manufacturing companies listed on the BEI in 2020 and 2022. Panel data regression analysis is the research tool of choice for this associative descriptive study. This study's population consists of 2020–2022 financial reports from BEI-listed food and beverage subsector manufacturing enterprises. Nonprobability sampling with a purposive sampling approach was used to collect the samples. Various statistical methods were employed to assess the impact of the study, including panel data regression analysis, t test and F test hypothesis testing, and Pearson product moment correlation and coefficient of determination analyses. There is a very strong correlation between return on equity (ROE) and Y (0.824) and a sufficient correlation (0.535) between debt to equity ratio and Y (0.535), according to the results of the analysis. The results of the determination analysis reveal that the debt-to-equity ratio and return on equity account for 99.2% of the variance in firm value, with the remaining 0.8% explained by factors that were not part of the study